Seismic assessment and strenghthening of existing residential reinforced concrete buildings - Kojouri, Samira Jilani (2010)
The ability of assessment tools to forecast the vulnerability of buildings to prevent collapse during an earthquake is essential for existing buildings. Seismic vulnerability assessment techniques are classified as quick and exact assessment categories. The aim of this study is to develop a numerical tool that can be used to evaluate existing reinforced concrete buildings against earthquake shaking. The vulnerability and retrofitting of low to medium rise reinforced concrete framed buildings (3, 4, 6 and 8 story) located in high zones of seismicity in Iran was carried out. In order to reduce the time of assessment, a quick check of buildings is essential. To achieve this purpose a numerical tool has been proposed based on FEMA 310 (Tier 2 and 3) for RC framed buildings in earthquake prone areas. Quick assessment methods do not have the ability to deduce the exact deficiencies of buildings. Nonlinear pushover analysis is a useful tool for the exact evaluation of existing buildings to give a good estimatimation of the overall displacement demands, base shears and plastic hinge formation. In order to determine the exact deficiencies of buildings the nonlinear static pushover analysis based on FEMA 356 was applied. The computational procedure to calculate the base shear force according to FEMA 356 is complicated and most of the time the effect of P-Δ is not considered. To fulfil this objective a computer program was developed to consider the effect of P-Δ on two and three dimensional models of RC framed buildings, and the capacity curve was obtained as a result of the nonlinear static analysis. The performance capacity level of RC framed buildings was found by idealizing the capacity curve. Hence the computer program developed idealizes the pushover curve according to FEMA 356. Consequently by using the developed program the buildings are evaluated in different performance levels. Results of pushover analysis were validated with the commercial software SAP2000. Due to the lack of codes to design the new retrofitted members a design procedure for new retrofitted members of buildings is provided. Eventually the appropriate retrofit is suggested for vulnerable buildings and members. The final results show that the quick assessment method is reliable at the global level. The pushover analysis is a useful tool to predict the failure mechanism of columns and beams in order to capture the exact assessment of buildings. Results of the retrofitted buildings show that the chevron steel bracing are more appropriate than the shear wall and RC jacketing due to the increase in strength without an increase in the weight of buildings and need for retrofitting of the foundation. For brittle structures with very weak strength, additional shear walls will be appropriate while for brittle structures with mechanism of strong beams and weak columns, RC jacketing will be effective.